(untitled) (Revista Apotheke, 2022)
This article falls within the scope of studies of the creative processes, and presents works by visual artists (Artist 1) and (Artist 2), who, coexisting as participants in the research project (Project Name / Institution), coordinated by Prof. Dr. (Advisor’s name), discovered similarities in their poetics and artistic practices. The works presented here articulate affective memories of the houses inhabited by the artists in their past, family narratives, relationships between memory and fabulation, the act of collecting everyday materials and restoration and sewing procedures, as well as dialogues between visual arts, literature and philosophy within their theoretical references. The physical and conceptual displacements mark the nomadisms in the very concept of home in the artists’ artworks, as a constant process of reconstruction of affections, desires and identities that is externalized and built through the manipulation and transmutation of materials.